STRATEGI EFEKTIF KOLABORASI SEKOLAH DAN KOMUNITAS DALAM MENDUKUNG MUTU PENDIDIKAN DASAR: STUDI KASUS DI SD MUSLIMIN PANYAWUNGAN 02 KABUPATEN BANDUNG: Effective Strategies for School–Community Collaboration in Supporting the Quality of Education in Primary Schools - Nugraha, Mulyawan Safwandy; Nur fadilah; Mardhiyah, Ira Siti Aenatum; Sumarna, Dedi; Manpaluti, Ikbal (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
Improving the quality of basic education is a persistent challenge, particularly for private schools in semi-urban areas with limited resources and weak community involvement. This study explores effective school-community collaboration strategies to support basic education quality through a case study at SD Muslimin Panyawungan 02, Bandung Regency. A qualitative approach with an intrinsic case study design was used. Data were gathered through participatory observation, in-depth interviews with the principal and teachers, and analysis of documentation. Findings show that collaboration includes financial support, participation in religious and social programs such as Islamic holiday events and mass circumcision, and involvement in parenting and character education through P5 (Project-Based Learning). Communication between school and parents occurs via formal meetings and digital platforms like WhatsApp, enhancing engagement. Key barriers include time constraints and limited parental understanding of their role, which are addressed through adaptive strategies. This study supports Epstein’s theory of school-family involvement and Senge’s learning organization concept, framing schools as collaborative learning centers. Inclusive, context-based collaboration proves essential for sustainably improving the quality of basic education.